An efficient parallel algorithm for list Viterbi decoding - Sánchez, Victoria; Peinado, Antonio M. (Signal processing, 2003)
There is nowadays an increasing interest in list Viterbi decoding, especially for transmission of audio and video over wireless channels. List Viterbi decoding outperforms conventional Viterbi decoding at the expense of an increase in complexity. In this paper, we propose an efficient parallel list Viterbi algorithm with lower computational complexity and memory requirements.